Neuroanatomical Correlates of Mild-to-Moderate Depression: Memory Ability Mediates the Association Between Gray Matter Volume and Antidepressant Treatment Outcome - Li, Hong; Wang, Junjie; Liu, Sha; Liu, Zhifen; Xu, Yong (Frontiers in Neuroscience, 2022)
Mild-to-moderate depression (MMD) is frequently encountered in clinical practice. Investigating the brain mechanism and its relationship with symptoms in patients with MMD can help us understand the occurrence and development of depression, thus optimizing the prevention and treatment of depression. Shugan Jieyu capsule (SG), a traditional Chinese medicine, is commonly used to ameliorate emotional and cognitive symptoms induced by patients with MMD. Combining clinical assessments and magnetic resonance imaging (MRI), we obtained the emotional and cognitive status of MMD patients and also investigated the structural and functional alterations in MMD patients following SG treatments. Structural MRI data indicated that MMD patients had significantly smaller gray matter volumes of the left thalamus, right thalamus and right amygdala than in healthy controls, and the right amygdala volume was negatively correlated with depression symptoms in MMD patients. Resting-state functional MRI data demonstrated that MMD patients exhibited decreased temporal coupling between the right amygdala and nucleus accumbens, which further associated with the severity of depression. Furthermore, right amygdala volume at baseline served as a significant predictor to identify the treatment outcome after 8 weeks SG treatment in the patients group, and importantly, the memory ability mediated the relationship from right amygdala volume to the treatment outcome. Overall, our results deepen our understanding of the relationship between brain morphology, cognitive ability, and the antidepressants treatment outcome for the MMD patients, which is hoped that will contribute to tailor a personalized method for treating MMD.